ALGEBRAIC NONLINEARITY IN VOLTERRA-HAMMERSTEIN EQUATIONS (Journal of Sciences, Islamic Republic of Iran)
Here a posteriori error estimate for the numerical solution of nonlinear Voltena- Hammerstein equations is given. We present an error upper bound for nonlinear Voltena-Hammastein integral equations, in which the form of nonlinearity is algebraic and develop a posteriori error estimate for the recently proposed method of Brunner for these problems (the implicitly linear collocation method).We also generalize this upper bound for nonlinear Volterra integro-differential and Volterra- Hammerstein integral equations of mixed type . Finally, several numerical examples are gken to show effectiveness of these bounds